Green Sports Products – Environmentally Friendly Efforts of some Sports Equipment and Sportswear Manufacturers. - Makara, Emese (International Journal of Engineering and Management Sciences, 2023)
In today's world, the issue of sustainability has become a cardinal problem on a global scale. The question of sustainability affects society, health, the economy, and the environment to a large extent. The examination of the environmental aspects of sustainability at the points where the sports sector interacts with the environment is considered a basis for research, and an increasing number of international studies and literature deal with this topic. Sports equipment and sportswear manufacturers operate through high numbers of multi-level global supply chains. They constantly strive to meet sudden changes in consumer demand, which results in high demand for raw materials and resources, waste and greenhouse gas emissions, and water consumption, all of which contribute to the most harmful environmental effects.The aim of this study is to present the environmental protection measures of Nike, Adidas, and Under Armour, multinational manufacturers of sports equipment and sportswear, aimed at raw material usage, waste management, minimizing water consumption, and reducing their carbon footprint, which they are increasingly applying as part of their business strategy.